2015
DOI: 10.1002/2015ms000471
|View full text |Cite
|
Sign up to set email alerts
|

Modeling stream temperature in the Anthropocene: An earth system modeling approach

Abstract: A new large-scale stream temperature model has been developed within the Community Earth System Model (CESM) framework. The model is coupled with the Model for Scale Adaptive River Transport (MOSART) that represents river routing and a water management model (WM) that represents the effects of reservoir operations and water withdrawals on flow regulation. The coupled models allow the impacts of reservoir operations and withdrawals on stream temperature to be explicitly represented in a physically based and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…This study adopts a physically based stream temperature model that is coupled with the Community Land Model (CLM) version 4.0 and a WM model (Li, Ruby Leung, Tesfa, et al, ), as shown in Figure . Individual components of Figure are explained below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adopts a physically based stream temperature model that is coupled with the Community Land Model (CLM) version 4.0 and a WM model (Li, Ruby Leung, Tesfa, et al, ), as shown in Figure . Individual components of Figure are explained below.…”
Section: Methodsmentioning
confidence: 99%
“…This alters the flow regime and seasonal variability of stream temperature (Yang et al, 2005) through the storage of water during high-flow periods and enhancement of low flows during the summer dry season (WWF, 2006;Ziv et al, 2012). On the contrary, water extraction that withdraws water directly from unregulated local streams reduces local discharge and tends to warm the stream especially in summer (Li, Ruby Leung, Tesfa, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Significant effort and progress have been made in large-scale representation and modeling of water management impact of reservoirs on streamflow (Hanasaki et al, 2008;Voisin et al, 2017Voisin et al, , 2013 and temperature (Li et al, 2015;Miara et al, 2017;Niemeyer et al, 2018;van Beek et al, 2012;van Vliet et al, 2012van Vliet et al, , 2013. In modeling stream temperature in the continental United States, Li et al (2015) suggested the inclusion of reservoir stratification models in river transport models to better represent stream temperature downstream of reservoirs. When it comes to understanding the stratification effect on stream temperature, most studies have focused on a single reservoir (for example, Bonnet et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Downstream of these reservoirs, the river shows a narrow seasonal range in observed temperature (approximately 4.0 to 10.0 °C), suggesting releases from the cooler hypolimnion of a stratified reservoir. Similarly, Li et al () simulated distributed river temperatures across the continental United States and had the poorest model performance below Hoover Dam which impounds Lake Mead, a stratified reservoir with a long residence time. As a result, Li et al () recommended incorporating thermal stratification into distributed river temperature models.…”
Section: Introductionmentioning
confidence: 99%